Trust The Fragile Foundation of Contemporary Biomedical Research - Kass, Nancy E. (The Hastings Center report, 1996)
It is widely assumed that informing prospective subjects about the risks and possible benefits of research not only protects their rights as autonomous decisionmakers, but also empowers them to protect their own interests. Yet interviews with patient-subjects conducted under the auspices of the Advisory Committee on Human Radiation Experiments suggest this is not always the case. Patient-subjects often trust their physician to guide them through decisions on research participation. Clinicians, investigators, and IRBs must assure that such trust is not misplaced.